2013
DOI: 10.1097/iae.0b013e318285cd9e
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Growth Factors and Cytokines in Patients With Dry and Neovascular Age-Related Macular Degeneration

Abstract: Clinical Age-Related Maculopathy Staging 3 dry AMD was associated with higher vascular endothelial growth factor levels than CARMS 5 neovascular AMD. Therefore, intraocular vascular endothelial growth factor concentrations do not seem to reflect choroidal neovascularization activity in neovascular AMD directly. Platelet-derived growth factor was decreased in most forms of AMD. The antiangiogenic endostatin was exclusively elevated in neovascular AMD, while thrombospondin 2 was reduced. Age-related macular dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
3
30
1
2
Order By: Relevance
“…In monkey eyes with laser-induced CNV, increased VEGF expression is detected in accumulating macrophages and migrating RPE cells in the CNV region [27]. Muether et al [11] reported that the intraocular VEGF level was elevated in intermediate dry AMD, but not in neovascular AMD. These findings suggest that VEGF contributes to CNV formation as the primary angiogenic signal, but VEGF levels do not reflect CNV activity [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In monkey eyes with laser-induced CNV, increased VEGF expression is detected in accumulating macrophages and migrating RPE cells in the CNV region [27]. Muether et al [11] reported that the intraocular VEGF level was elevated in intermediate dry AMD, but not in neovascular AMD. These findings suggest that VEGF contributes to CNV formation as the primary angiogenic signal, but VEGF levels do not reflect CNV activity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Muether et al [11] reported that the intraocular VEGF level was elevated in intermediate dry AMD, but not in neovascular AMD. These findings suggest that VEGF contributes to CNV formation as the primary angiogenic signal, but VEGF levels do not reflect CNV activity [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of VEGF have been found in the aqueous and vitreous from subjects with DR (Endo et al 2000), neovascular age-related macular degeneration (AMD) (Jonas et al 2012;Miao et al 2012;Muether et al 2013), retinal vein occlusion (RVO) (Feng et al 2013) and retinopathy of prematurity (ROP) (Velez-Montoya et al 2010). It has also been shown that IOP level as well as success rates of surgical intervention in NVG subjects were associated with the intraocular level of VEGF ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors (de Oliveira Dias et al 2011;Sasamoto et al 2012;Zhou et al 2013), inflammatory cytokines (Amadi-Obi et al 2012;Hoh Kam et al 2013;Whitcup et al 2013) and adhesion molecules (Grunin et al 2012;Juel et al 2012;Muether et al 2013) are important in angiogenesis and fibrosis formation. Their roles in inducing neovascular growth have been proved.…”
Section: Introductionmentioning
confidence: 99%